Application of nucleic acid mimics in fluorescence in situ hybridization - Oliveira, Ricardo (2021)
Traditionally, RNA and DNA probes are used in fluorescence in situ hybridization (FISH) methods for microbial detection and characterization of communities structure and diversity. However, the recent introduction of nucleic acid mimics (NAMs) has improved the robustness of the FISH methods in terms of sensitivity and specificity. Several NAMs have been used, of which the most relevant are peptide nucleic acid (PNA), locked nucleic acids (LNA), 2-O-methyl RNA (2OMe), and phosphorothioates (PS). In this chapter, we describe a protocol using PNA and LNA/2OMe probes for microbial detection by FISH, pointing out the differences between them. These protocols are easily adapted to different microorganisms and different probe sequences.